ELEMENTARY SCHOOL TEACHERS' SCIENCE LITERACY CAPABILITIES IN DIY AND THEIR IMPLEMENTATION IN PREPARATION FOR THE ASESMEN STANDARDISASI PENDIDIKAN DAERAH (ASPD) - Pangesti, Nindiasari Agung; Jumadi, Jumadi (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2022)
This research analyzes the science literacy skills of elementary school teachers in the Special Region of Yogyakarta (DIY) and their implementation in preparing the Regional Education Standard Assessment (ASPD). Teachers' science literacy skills significantly impact the quality of primary education, especially in preparing for ASPD. PISA defines science literacy as the ability to interact with science-related issues and ideas of science as a reflective citizen. This study uses a qualitative approach with descriptive analysis methods. The respondents in this study were five elementary school teachers from various schools in DIY—the data collection technique for teachers' science literacy skills used science literacy questions from PISA 2015. Meanwhile, data on the implementation of science literacy were obtained using a Likert scale. The study results show that elementary school teachers in DIY have science literacy skills with a score of 44.3%. Teachers who possess science literacy skills have generally implemented them in their teaching. However, some teachers have yet to receive science literacy training and implement it in the classroom.